Three-dimensional anatomical diagram of human head - West, James J.; Yaggy, L. W. (Levi W.) (The Book of Health, 1885)
Three-dimensional color diagram of human head consisting of hinged, paper flap overlays. A form of anatomical illustration in use as early as 1538, the overlays progressively fold back to reveal the interior and major components of the head, skull, and brain, including cranial bones, teeth, muscles, spinal cord, and nasal passages. The final image is a phrenological illustration depicting the parts of the brain purported to control one's propensities towards a variety of sentiments and emotions, including hope, cautiousness, spirituality, and combativeness. This diagram appears opposite page 870 in The Book of Health (1898).
Keywords: Skull--Study and teaching; Human anatomy; Phrenology; Medicine, Popular; Phrenology--Study and teaching; Human anatomy--Study and teaching